Synthesis, Characterization and Pharmacodynamics of Vitamin‐B12‐Conjugated Glucagon‐Like Peptide‐1. Issue 4 (30th November 2012) - Clardy‐James, Susan; Chepurny, Oleg G.; Leech, Colin A.; Holz, George G.; Doyle, Robert P.
<x xml:space="preserve">Abstract</x> Clearing the way: Glucagon‐like peptide‐1 (GLP‐1) receptor agonists are proving a potent weapon in the treatment of type II diabetes. A new vitamin B12–GLP‐1 conjugate is investigated and shown to have insulinotropic properties similar to the unmodified peptide. These results are critical to the exploitation of the vitamin B12 oral uptake pathway for peptide delivery.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>